2015
DOI: 10.1021/acs.jpca.5b07019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modes and Dynamics of HCl and DCl Guests of Gas Clathrate Hydrates

Abstract: Recent years have yielded advances in the placement of unusual molecules as guests within clathrate hydrates (CHs) without severe distortion of the classic lattice structures. Reports describing systems for which observable but limited distortion does occur are available for methanol, ammonia, acetone, and small ether molecules. In these particular examples, the large-cage molecules often participate as non-classical guests H-bonded to the cage walls. Here, we expand the list of such components to include HCl/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…Within the five independent simulations at each temperature, we observed a total of four hydrogen-interchange events at 250 K and eight hydrogen-interchange events at 260 K, which correspond to a hydrogen-interchange rate of ∼10 4 s –1 per water molecule, whereas hundreds of such events, which corresponds to a hydrogen-interchange rate of ∼10 6 s –1 per water molecule, can be observed at the high temperature of 300 K. With the measured the hydrogen-interchange rate, we can estimate the associated free energy of activation using eq . Figure shows the linear regression results of the measured hydrogen-interchange rates (ln­( k / T )) versus temperatures (1/ T ), from which we can calculate that the 95% confidence interval for the rate of the hydrogen interchange is 1.3 × 10 5 –2.4 × 10 5 s –1 per water molecule, and the 95% confidence interval for the associated free energy of activation is 38.2–39.4 kJ/mol at 270 K. These values are comparable to previous results from all-vapor experiments, supersonic nozzle experiments, and thermodynamics calculations , of clathrate hydrates with hydrogen-bonding guests but under much lower temperatures, indicating the effects of the hydrogen-bonding guests on inducing the defect formation and accelerating the mass diffusion in gas hydrates. Note while previous experimental studies using NMR techniques have studied the water reorientation processes within gas hydrate systems, for example, the activation energy of water reorientations in THF hydrates is determined to about 31 kJ/mol, ,, the particular type of water reorientations discussed in this paper may not be identified directly in these NMR experiments where all the possible water orientations are sampled over time.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Within the five independent simulations at each temperature, we observed a total of four hydrogen-interchange events at 250 K and eight hydrogen-interchange events at 260 K, which correspond to a hydrogen-interchange rate of ∼10 4 s –1 per water molecule, whereas hundreds of such events, which corresponds to a hydrogen-interchange rate of ∼10 6 s –1 per water molecule, can be observed at the high temperature of 300 K. With the measured the hydrogen-interchange rate, we can estimate the associated free energy of activation using eq . Figure shows the linear regression results of the measured hydrogen-interchange rates (ln­( k / T )) versus temperatures (1/ T ), from which we can calculate that the 95% confidence interval for the rate of the hydrogen interchange is 1.3 × 10 5 –2.4 × 10 5 s –1 per water molecule, and the 95% confidence interval for the associated free energy of activation is 38.2–39.4 kJ/mol at 270 K. These values are comparable to previous results from all-vapor experiments, supersonic nozzle experiments, and thermodynamics calculations , of clathrate hydrates with hydrogen-bonding guests but under much lower temperatures, indicating the effects of the hydrogen-bonding guests on inducing the defect formation and accelerating the mass diffusion in gas hydrates. Note while previous experimental studies using NMR techniques have studied the water reorientation processes within gas hydrate systems, for example, the activation energy of water reorientations in THF hydrates is determined to about 31 kJ/mol, ,, the particular type of water reorientations discussed in this paper may not be identified directly in these NMR experiments where all the possible water orientations are sampled over time.…”
Section: Resultssupporting
confidence: 83%
“…The transient defects generated during these processes may facilitate guest rotational and translational motions in the gas hydrate cages and hence have implications for the unusual behavior of the thermal conductivity and mechanical properties of gas hydrates. , Note similar rotation processes have been observed in ice Ih when the central water molecules are surrounded by a Bjerrum L-type defect . This rotation process is also essential to the proton transport and the isotopic exchange processes as demonstrated before. ,,, It has been shown that the hydrogen-bonding guests, such as small ether molecules, H 2 S, etc., can enhance the defect concentration in gas hydrates and catalyze the formation of gas hydrates, , which are consistent with the all-vapor gas hydrate formation experiments with various guest molecules. In future studies it would be interesting to investigate the possible role of the guest molecules in inducing and stabilizing the transient defects in gas hydrates.…”
Section: Resultssupporting
confidence: 74%
“…Furthermore, they observed a doublet of the THF absorption feature at very low temperatures (13 K), which was attributed to THF in two unequal positions within the hexakaidecahedral cages of the hydrate structure. 25 Recent publications observed the feature at 1073 cm À1 for a double clathrate hydrate consisting of THF and HCN at 130 K, 43 and at 1073 cm À1 for a 90% deuterated THF and HCN binary clathrate hydrate at 170 K. 44 The weak absorption feature centered at 1072 cm À1 , which is present in the H 2 O hydrate spectrum in Fig. 4 and evident in more detail in Fig.…”
Section: -19mentioning
confidence: 87%